The Application of Mind Mapping Method in Improving Learning Outcomes in Islamic Education - Nugroho, Awal Aqsha (Lembaga Pendidikan Hikmatun Najah (LPHN) Blora, 2024)
Teaching methods as tools to create an effective teaching and learning process are very important. Based on observations at SMPN 2 Ngadirojo, it was found that the teaching of Islamic Religious Education does not significantly improve students' learning outcomes, due to the dominant use of the lecture method, which causes students to become passive in the learning process. The assessment of the learning outcomes achieved by the students is still below the criteria for achieving the learning objectives. This research aims to determine the improvement in student learning outcomes in Islamic Education and Character Education using the Mind Mapping method. The research method used is classroom action research. Based on the data analysis from Cycle I and Cycle II, it can be stated that the learning outcomes of students in Islamic Religious Education show a positive response to the application of the Mind Mapping method on the material of Islamic ethics in social interactions and communication, which increased to 83%, on behalf of the school, the results of this research can be used as input to implement variations in teaching methods to improve the quality of education and learning activities. For educators, the subject of Islamic Religious Education and Character Education, the Mind Mapping method can be used as an alternative to enhance the quality of learning by aligning the designed learning with variations in teaching and the selection of teaching methods. This aims to anticipate the boredom experienced by the students.